2005
DOI: 10.1111/j.0303-6987.2005.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of angiomyxolipoma (vascular myxolipoma) of subcutaneous tissue

Abstract: Angiomyxolipoma (vascular myxolipoma) is a recently described rare variant of lipoma, four cases of which have been reported to date. Microscopically, the lesion consists of adipose tissue without lipoblasts, extensive myxoid areas, and numerous blood vessels. The main differential diagnosis of this lesion is myxoid liposarcoma, and other adipocytic lesions such as myxolipoma, myxoid spindle cell lipoma should be included. We report two cases of angiomyxolipoma located in the subcutaneous tissue of the forearm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…This lesion shares many clinical and pathological features of myxoid spindle cell lipoma, solitary fibrous tumour with myxoid change, and angiomyxolipoma [3][4][5]. It is characterised by a mixture of spindle and stellate cells, mature adipose tissue, and abundant myxoid stroma with prominent collagenisation.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This lesion shares many clinical and pathological features of myxoid spindle cell lipoma, solitary fibrous tumour with myxoid change, and angiomyxolipoma [3][4][5]. It is characterised by a mixture of spindle and stellate cells, mature adipose tissue, and abundant myxoid stroma with prominent collagenisation.…”
Section: Introductionmentioning
confidence: 84%
“…There were no mitoses in the tumour cells and no cytological atypia, indicating that the tumour was benign. It lacked the vascular component of angiomyxoma where spindle stromal cells, in addition, fail to stain for CD34 [5].…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, Mai et al [3] reported a case of a rare variant of lipoma of the spermatic cord in a 34 year-old man, characterized by a proliferation of adipocytes associated with a myxoid background and multiple blood vessels and designated it as angiomyxolipoma. Since then, ten cases of this rare variant have been reported in the English literature, [3][4][5][6][7][8][9][10][11][12] which have been located mainly in subcutaneous tissues (eight cases), one case occurred as subungual angiomyxolipoma and the other developed in the spermatic cord. Our patient is the first case of angiomyxolipoma originated within the oral tissues (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Histological differential diagnosis of angiomyxolipoma includes benign lesions, such as SCL and its variants (myxoid, vascular, pseudoangiomatous), dendritic fibromyxolipoma, myxolipoma, angiolipoma, superficial angiomyxoma, angiomyofibroblastoma, cellular angiofibroma, lipoblastoma, benign mesenchymoma as well as aggressive angiomyxoma; malignant lesions to be discarded includes myxoid liposarcoma and low-grade myxofibrosarcoma [8].…”
Section: Discussionmentioning
confidence: 99%
“…It presents as a well-circumscribed tumor characterized by an admixture of mature adipose tissue, paucicellular myxoid stroma, and an abundance of thin-and thick-walled blood vessels. Until now only eight cases had been reported in literatures [2][3][4][5][6][7][8] . Here we report another case of angiomyxolipoma arising in subcutaneous tissue.…”
Section: Introductionmentioning
confidence: 99%